The survey of clinical fundal height assessment among the obstetric practitioners / Nadzratulaiman Wan Nordin ... [et al.] - Wan Nordin, Nadzratulaiman; Abdullah, Bahiyah; Parai, Farhana; Domadi, Siti Masyitah; Isa, Mohamad Rodi (Faculty of Medicine, 2025)
Introduction: Clinical f undal height assessment (symphysis-f undal height (SFH), landmark method and f inger method) is a common practice among obstetric practitioners despite a lack of evidence on its use. This study aims to determine the attitude and practice of the three methods of clinical estimation of f undal height among obstetric practitioners. Methods: Thi s was a cross-sectional study involving 258 doctors who were practising obstetrics in Malaysia, who were recruited through convenience sampling. A validated self -administered questionnaire consisting of background details, and questions on attitude and practice on clinical estimation of f undal height was used. Results: From the total of 258 respondents, 237 (91.8%) agreed that estimating f undal height clinically is important and 230 (89.1%) respondents agreed this should be taught to medical students. In addition, 189 (73.3%) and 155 (60.1%) participants f elt that SFH should be supplemented with the landmark method and f inger method respectively. There were 230 (89.1 %) respondents practising clinical f undal height assessment, with 167/230 (72.6%) practising SFH measurement, 123/230 (53.5%) practising landmark method, and 116/230 (50.4%) practising f inger method. This study also f ound that 96/230 (41.7%) practitioners use a single method f or their practice and 134/230 (48.3%) practitioners use a combination of methods. The clinical f undal height assessment also was demonstrated to be associated with gender (p=0.01), highest degree obtained (p=0.00), current place of practice (p=0.00), and current post (p=0.00). Conclusion: The majority of obstetrics practitioners agree that clinical f undal height assessment is important and perf orm it in their daily practice, however, the methods used vary.